Quantum gravitational applications of nuclear, atomic and astrophysical phenomena - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2016)
By following the old concept of â€œgravity is having a strong coupling at nuclear scaleâ€ and considering the â€˜reduced Planckâ€™s constantâ€™ as a characteristic quantum gravitational constant, in this letter we suggest that: 1) There exists a gravitational constant associated with strong interaction, Gs~3.328x1028 m3/kg/sec2. 2) There also exists a gravitational constant associated with electromagnetic interaction, Ge~2.376x1037 m3/kg/sec2.Based on these two assumptions, in a quantum gravitational approach, an attempt is made to understand the basics of final unification with various semi empirical applications like melting points of elementary particles, strong coupling constant, proton-electron mass ratio, proton-neutron stability, nuclear binding energy, neutron starâ€™s mass and radius, Newtonian gravitational constant, Avogadro number and molar mass unit. With further research and investigation, a practical model of â€˜quantum gravitational string theoryâ€™ can be developed.